2012
DOI: 10.1158/1940-6207.capr-12-0230
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Promotion by Parthenolide: Epigenetic Modulation of p21

Abstract: The promotion stage in the multistep process of epidermal tumorigenesis is NF-kB-dependent, epigenetically regulated, and reversible, thus, a suitable target for chemoprevention. We investigated whether the NF-kB inhibitor, parthenolide, currently in cancer clinical trials, attenuates tumor promotion by modulating the epigenetically regulated NF-kB target genes, p21 and cyclin D1.Parthenolide selectively inhibited the growth of neoplastic keratinocytes while sparing normal ones. Specifically, in JB6Pþ cells, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
5
13
0
Order By: Relevance
“…Figures 2 –4 represent the cell viability percentages of ruthenium(III)-Schiff base complexes and parthenolide drug against TK-10, UACC-62, and MCF-7 cell lines, at different concentrations of ruthenium(III) compounds or parthenolide. A high level of antiproliferative potentials against the studied cell lines was exhibited by parthenolide in accordance with earlier reports [45]. The obtained results revealed that treatment of cell lines with different concentrations of Ru(III)-Schiff base complexes efficiently affected cell viability towards MCF-7 cells, as displayed in Figures 2 –4 and Table 1.…”
Section: Resultssupporting
confidence: 90%
“…Figures 2 –4 represent the cell viability percentages of ruthenium(III)-Schiff base complexes and parthenolide drug against TK-10, UACC-62, and MCF-7 cell lines, at different concentrations of ruthenium(III) compounds or parthenolide. A high level of antiproliferative potentials against the studied cell lines was exhibited by parthenolide in accordance with earlier reports [45]. The obtained results revealed that treatment of cell lines with different concentrations of Ru(III)-Schiff base complexes efficiently affected cell viability towards MCF-7 cells, as displayed in Figures 2 –4 and Table 1.…”
Section: Resultssupporting
confidence: 90%
“…Parthenolide demonstrated high levels of antiproliferative effect against all cell lines, in accord with previous reports [70]. The values of the concentration of the compounds for 50% inhibition (IC 50 ) were obtained from non-linear regression analysis of dose response data for the compounds tested and are presented in 5), which is in agreement to their order of in vitro DPPH scavenging ability of the Ru(III) complexes.…”
Section: Antiproliferative Activity Evaluationsupporting
confidence: 87%
“…The sesquiterpene lactones Parthenolide and Costunolide were originally identified as inhibitors of the NF-κB pathway (Bork, Schmitz, Kuhnt, Escher, & Heinrich, 1997), but their roles in modulating the tyrosination-detyrosination cycle have also recently been described (Barisic & Maiato, 2016; Fonrose et al, 2007; Whipple et al, 2013). In the case of Parthenolide, it has notable anticancer properties and its activity has been linked to several cellular processes including apoptosis (Gopal, Arora, & Van Dyke, 2007), DNA methylation (Liu et al, 2009), p21 signalling (Ghantous et al, 2012) and the regulation of TNF-α (Zhang et al, 2017), amongst others. Since Parthenolide has highly reactive groups that confer high levels of non-specificity, its careful use at the correct dose, as well as proper storage and avoidance of freeze-thaw cycles is highly recommended.…”
Section: Section 1 - Modulation Of the Detyrosination/tyrosination Cymentioning
confidence: 99%